A unique case of coats plus syndrome and dyskeratosis congenita in a patient with CTC1 mutations. (3rd July 2020) - Han, Elaine; Patel, Nimesh A.; Yannuzzi, Nicolas A.; Laura, Diana M.; Fan, Kenneth C.; Negron, Catherin I.; Prakhunhungsit, Supalert; Thorson, Willa L.; Berrocal, Audina M.
ABSTRACT: Coats plus syndrome (CP) is a rare condition characterized by bilateral exudative retinal telangiectasias with associated systemic disorders primarily affecting the brain, bone and gastrointestinal tract due to a mutation in the CTC1 gene. CTC1 mutations are also known to cause dyskeratosis congenita (DC), which is an inherited bone marrow failure syndrome characterized by skin pigmentation abnormalities, nail dystrophy, and oral leukoplakia. This is the first reported case of a patient diagnosed with both CP and DC caused by compound heterozygous CTC1 gene mutations. Moreover, one of the variant mutations found in this patient has never been published before.